Examen especial a las cuentas del activo de la Cooperativa de Ahorro y Crédito “Sumak Kawsay” ltda., provincia de Cotopaxi, cantón Latacunga, periodo del 01 de enero al 31 de diciembre 2015 - Anchatuña Viracocha, Angelica Marisol (2016)
This research applied a special examination to asset accounts at the credit and saving SUMAK KAWSAY cooperative in order to verify the accounting process and how the resources of the entity available are used it was used Descriptive research non-experimental methodology as well as inductive deductive method, analytic and synthetic techniques such as direct observation in the institution, the interview addressed to the enterprise General Manager and finally the employees is surveys from different departments and other members of the institution in order to verify whether the accounting processes transactions in the period 2015 were carried out in an efficiently and effectively way allowing having reasonable results in the General ledger….